(untitled) (Texas Journal of Medical Science, 2023)
Acute respiratory viral infections (ARVI) are widespread infectious diseases, cause significant economic damage and therefore are not only a serious medical, but also the most important socio-economic problem for humanity. This group of diseases accounts for up to 90% of all infectious morbidity. Mostly children and people over 60 years of age fall ill - the so-called risk groups for the incidence of ARVI. Every adult suffers from influenza or other acute respiratory viral infections on average 2-4 times a year, a schoolchild - 4-5 times, a preschool child - 6 times, a child of the first year of life has from 2 to 12 episodes of acute respiratory viral infections. The polyetiology of ARVI pathogens and the variability of viruses involved in the epidemic process, complications after an illness, necessitate the search for new diagnostic methods and optimization of treatment and preventive measures. Modern approaches to the treatment of influenza and acute respiratory viral infections of other etiologies are reduced to the use of complex drugs that combine antiviral, immunomodulatory, symptomatic and pathogenetic effects.